Tourism supply side: the case of Niah Cave's Swiflets - Awang, Khairil Wahidin; Mustapha, Mazlina; Abdullah, Hasan (Science Publishing Corporation, 2018)
Often studies on tourism come from the consumer perspective. However, this study focuses on the supply side of the industry using the wonders of Niah Cave which is located in interior Sarawak, Malaysia. Amongst others, Niah Cave has hundred thousands of swiftlet population and the world's famous archaeological site to attract tourists. This article explores a venue whereby the tourism's supply side, in this instance, the swiftlet population could be bridged with the industry's consumer side. The evolvement of sustainability conscious consumers, particularly in the millennium era results in the advocation of consumption in a more sustainable manner, irrespective whether the products are manmade or in the forms of the natural environment. An interpretative research method with the like of observation and semi-structured indepth interviews formed the data gathering tool. The Niah Cave was explored in late January 2017. Findings show that Niah Cave was literally on the tourist map due to its world's famous archaeological site. The huge population of swiftlets with their nests attracted harvesters for decade. The processes of harvesting these nests which remarkably endured through climbing bamboo ladders and dangling ropes from cave ceilings, hundreds feet from the cave floor, charmed tourists.